Spin, confinement, localization and supersymmetry - Cirilo-Lombardo, Diego Julio (Вопросы атомной науки и техники, 2012)
New mechanism of localization of fields in a particular sector of a special supermanifold is proposed and described, based on previous works of the authors. Different aspects of this new mechanism are discussed as an alternative to confinement in elementary particle physics and to the Randall-Sundrum scenarios in warped manifolds.